No Journals, No Evidence-Based Practice: Research Inaccessibility Affects Many Nurses. Issue 6 (November 2019) - Rogers, Melanie
Abstract : It is a significant challenge to maintain up-to-date knowledge for evidence-based practice when so many nurses have lost access to research publications via the health library after graduation from nursing school. Nurses may be practicing based on out-of-date information. There is risk of harm to patients when nurses are unable to access and evaluate evidence for recommendations for high-quality nursing care. In this guest editorial, Melanie Rogers explains the problem and offers several viable solutions. She has launched a campaign about this topic on Twitter: #NoJournalsNoEBP @MRogersRN.